The Effect of Smartphone Use Intensity on High School Students' Learning Motivation - Habiburrahman, Habiburrahman; Daud, Muh; Halima, Andi (Polteknik Ilmu Pemasyarakatan, 2024)
Learning motivation is the impetus that arises from within individuals to learn. Learning motivation is one of the important factors that individuals must possess in their efforts to achieve good learning outcomes. One of the factors that influences learning motivation is usage. This study aims to determine the effect of smartphone usage intensity on high school students' learning motivation. This study uses a quantitative regression approach. The respondents in this study were 196 students of grade XI at SMA Negeri 2 Pinrang (n=196, 49 males and 147 females). The sampling technique used was cluster random sampling. The results of the study indicate that there is no significance between smartphone usage intensity and high school students' learning motivation (p: X to Y1 = 0.205. X to Y2 = 0.181. X to Y3 = 0.384), which means there is no influence between smartphone usage intensity and intrinsic, extrinsic, and amotivation motivation in students. In this case, smartphone usage intensity is not significant in the process of whether learning motivation emerges or not in students. The implications of this study show differences in results compared to previous studies that stated an influence between smartphone usage and students' learning motivation. This study is expected to serve as a basis for further researchers who investigate similar variables.